Cultural attitudes, economic shocks and political radicalization - Annie Tubadji (The Annals of Regional Science, 2019)
The present paper focuses on the emergence and consequences of the so-called ‘Dogville Effect’, i.e., the negative socioeconomic and spatial impacts caused by radicalization of cultural attitudes in a region. After a conceptual and historical outline of this phenomenon, we present an empirical case, viz. the rise of the ultra-right-wing party in Greece, Chrysi Avgi. We analyze the party’s spatial dispersion and its aftermaths in the period 1993–2015, using both local and regional election results. Spatial-economic controls are derived from the EUI (European University Institute, Florence) regional database. We employ a 2SLS approach (with historical voting results from 1974 as an instrumental variable) and a difference-in-differences approach with a propensity score matching. Our findings show that there exists a cultural persistence in the local share of ultra-right-wing support. The growth in this radicalization, however, is predominantly determined by the shrinking regional household welfare caused by exogenous forces in our model. Finally, the ‘Dogville Effect’, i.e., a further impoverishment of more radicalized localities, seems to be present in Greece, in the vein of the notion of Myrdal’s vicious circles.